Performance Evaluation of Single Stage Flash Evaporation Desalination Unit Integrated with a Parabolic Trough Solar Collector for Basrah City Climate, Iraq - Salim, M. Kareem; Sultan, Hussien S.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2024)
Solar energy is the most suitable among all renewable energy options for competing with fossil fuels in desalination due to its ability to utilize both heat and power for the process. In this study, the Parabolic Trough Solar Collector (PTSC) for powering a Single Stage Flash (SSF) desalination unit was proposed for Basrah city climate, Iraq. The desalination system comprises two directly coupled sub-systems: the PTSC and the SSF desalination unit. The preheated feed brine water coming from condenser was used as a Heat Transfer Fluid (HTF) for PTSC, which gets heated to a desired temperature referred to as the Top Brine Temperature (TBT). The numerical simulations were performed via EBSILON professional 16.02 (2022) software. The effects of TBT, mass flowrate of feed brine water to get the desired TBT, solar collector area, and vacuum pressure inside flash chamber on the performance of the desalination system was studied. A major finding of the current study can be summarized as follows: The collector efficiency is enhanced eventually as TBT increases. The maximum values of distillate water in June are around 5.5, 4.56, 3.69, 2.75 and 1.85 kg/h for 12.408, 10.434, 8.3472, 6.26, and 4.1736 m² collector area respectively, when TBT 107 °C and vacuum pressure 40 kPa. For 1.598 m² collector area, the total distillate in the 1st of June amounted to 7.9 kg, with an average production rate of around 0.7 kg/h. The solar SSF system's productivity per solar collector unit area at 20 kPa, 15 kPa, and 10 kPa vacuum pressures was 4.7 kg/day/m², 5.3 kg/day/m², and 6.25 kg/day/m², respectively. The average Performance Ratio (PR) values are determined to be 0.694, 0.577, and 0.491 for 10 kPa, 15 kPa, and 20 kPa, respectively. These results are very acceptable when compared with an existing literature.